Reading Culture with Medium Gelis Tree (School Literacy Movement) in Develop Students' Civic Intelligence - Nurul Aini, Dinda; ., Sapriya (International Journal of Engineering and Technology, 2018)
The objective of this research is to describe the development of students' competencies on civic intelligence as a result of reading culture using Gelis Tree (Gerakan Literasi Sekolah or School Literacy Movement). This research was conducted based on regulation issued by Ministry of Education and Culture No. 23 in 2015 on the Development of Virtuous, which contains materials on Development Potential of Learners as a Whole such as 15 minutes daily reading activity for student. This reading activity is meant to create a reading culture and to form the virtuous and character revolution for Indonesian people. The government named this movement as Gerakan Literasi Sekolah (GLS) or School Literary Movement. To facilitate the control on GLS, Lembaga Penjamin Mutu Pendidikan (LPMP) or Institute for Quality Assurance on Education in West Java created a tool or medium called Pohon Gelis or Gelis Tree. Based on the previously described regulation, the effect of reading culture implementation on the development of students' competencies on civic intelligence is investigated. This research utilized descriptive analytical method with qualitative approach. The subjects in this research were students of Sekolah Menengah Pertama Negeri 3 (SMPN 3) or National Junior High School 3, Subang, as the pioneering and referenced school that implementing Gelis tree in GLS program. The participants in this research consisted of pioneering teachers, Civics teachers, class teachers, and students. Research instrument consisted of observation, interviews, study on documents, and questionnaire. Data processing was performed in three stages: data reduction, data presentation, and verification with decision making. From the results it is shown that the implementation of reading culture with Gelis Trees enhanced developed the competencies of students' civic intelligence. The most developed aspects were intelligence quotient, emotional intelligence, and moral intelligence. It also concluded that in addition to shaping the character and virtuous, reading culture also improved civic intelligence.
Keywords: Reading Culture; School Literacy Movement; Civic Intelligence